Factors influencing bacterial adhesion to contact lenses - Dutta, Debarun (Molecular Vision, 2012)
The process of any contact lens related keratitis generally starts with the adhesion of opportunistic pathogens to contact lens surface. This article focuses on identifying the factors which have been reported to affect bacterial adhesion to contact lenses. Adhesion to lenses differs between various genera/species/strains of bacteria. Pseudomonas aeruginosa, which is the predominant causative organism, adheres in the highest numbers to both hydrogel and silicone hydrogel lenses in vitro. The adhesion of this strain reaches maximum numbers within 1h in most in vitro studies and a biofilm has generally formed within 24 h of cells adhering to the lens surface. Physical and chemical properties of contact lens material affect bacterial adhesion. The water content of hydroxyethylmethacrylate (HEMA)-based lenses and their iconicity affect the ability of bacteria to adhere. The higher hydrophobicity of silicone hydrogel lenses compared to HEMA-based lenses has been implicated in the higher numbers of bacteria that can adhere to their surfaces. Lens wear has different effects on bacterial adhesion, partly due to differences between wearers, responses of bacterial strains and the ability of certain tear film proteins when bound to a lens surface to kill certain types of bacteria.